2016
DOI: 10.1155/2016/6146901
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Ultrasound and CT Increased Diagnostic Value in Female Patients with Pelvic Masses

Abstract: Purpose. The current study aimed to evaluate whether combined application of ultrasound and CT had increased Diagnostic Value in Female Patients with Pelvic Masses over either method alone. Patients and Methods. 240 female patients with pelvic masses were detected preoperatively with ultrasound and CT prior to surgery. The sensitivity, specificity, and accuracy of ultrasound, CT, and combined ultrasound/CT application were evaluated, respectively. Results. The sensitivity, specificity, and accuracy of ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our findings correlate with Liu Y et al 3 and Firoozabadi et al 4 study which showed youngest 18 years and most elderly 77 yr. Majority of patients included were above 40 years in Liu Y et al 3 study.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings correlate with Liu Y et al 3 and Firoozabadi et al 4 study which showed youngest 18 years and most elderly 77 yr. Majority of patients included were above 40 years in Liu Y et al 3 study.…”
Section: Discussionsupporting
confidence: 92%
“…CT/MRI not only detected the tumor missed by TAS but also detected the missed cystic components of the solid cystic tumors. In a study done by Yan Liu et al ., the sensitivity, specificity and accuracy of combined application of ultrasound and CT were 89, 94.7 and 91.7% (16), which were higher than those of either ultrasound or CT in the diagnosis of pelvic mass. In the evaluation of adnexal masses indeterminate on ultrasound, assessment with contrast-enhanced MRI increases sensitivity to 81% and specificity to 98%.…”
Section: Discussionmentioning
confidence: 82%
“…Ultrasound is superior as the first diagnostic tool due to its relatively easy availability, high sensitivity, lack of radiation exposure, and low cost. In a study of 240 patients with pelvic masses, ultrasound, CT, and combined ultrasound/CT application were evaluated, and accuracy of them were 68.8%, 85.0%, and 91.7%, respectively [ 12 ]. Therefore, when a pelvic mass is suspected on initial testing with ultrasound, a combination of ultrasound with CT might prove to be a useful diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%